Experiencing the Apocalypse at the limits of alterity - Hongisto, Leif. (Biblical Interpretation Series, 2010)
Applying current narrative criticism to the study of the Apocalypse, Hongisto underscores the oral nature of the narrative vis-à-vis the roles of the readers/listeners. EXPERIENCING THE APOCALYPSE AT THE LIMITS OF ALTERITY probes the interplay of meaning creation as readers/listeners encounter the narrative. The author shows how readers/listeners alike partake in the narrative design and become constructors of the narrative, given their own life experiences. Thus, the overarching reading context assists in the creation of a narrativity for the text. The form of the Apocalypse along with its imagistic quality convey a message that is not primarily cognitive, but is delivered and grasped by a sense of alterity encompassing the imaginary world of the text and the real world of the readers/listeners.